Associations Between Physician Empathy, Physician Characteristics, and Standardized Measures of Patient Experience. (October 2017) - Chaitoff, Alexander; Sun, Bob; Windover, Amy; Bokar, Daniel; Featherall, Joseph; Rothberg, Michael B.; Misra-Hebert, Anita D.
Abstract : Purpose: To identify correlates of physician empathy and determine whether physician empathy is related to standardized measures of patient experience. Method: Demographic, professional, and empathy data were collected during 2013–2015 from Cleveland Clinic Health System physicians prior to participation in mandatory communication skills training. Empathy was assessed using the Jefferson Scale of Empathy. Data were also collected for seven measures (six provider communication items and overall provider rating) from the visit-specific and 12-month Consumer Assessment of Healthcare Providers and Systems Clinician and Group (CG-CAHPS) surveys. Associations between empathy and provider characteristics were assessed by linear regression, ANOVA, or a nonparametric equivalent. Significant predictors were included in a multivariable linear regression model. Correlations between empathy and CG-CAHPS scores were assessed using Spearman rank correlation coefficients. Results: In bivariable analysis (n = 847 physicians), female sex ( P < .001), specialty ( P < .01), outpatient practice setting ( P < .05), and DO degree ( P < .05) were associated with higher empathy scores. In multivariable analysis, female sex ( P < .001) and four specialties (obstetrics–gynecology, pediatrics, psychiatry, and thoracic surgery; all P < .05) were significantly associated with higher empathy scores. Of the seven CG-CAHPS measures, scores on five for the 583 physicians with visit-specific data and on three for the 277 physicians with 12-month data were positively correlated with empathy. Conclusions: Specialty and sex were independently associated with physician empathy. Empathy was correlated with higher scores on multiple CG-CAHPS items, suggesting improving physician empathy might play a role in improving patient experience.